Functional characterization of EjAP1-like1 reveals its role in floral development and flowering time regulation in loquat (Eriobotrya japonica) - Wang, Yifang; Zhao, Chongbin; Yang, Xiaoyan; Wang, Bin; Peng, Ze; Yang, Xianghui; Ma, Chongjian; Yuan, Yuan; Jiang, Yuanyuan (Frontiers in Plant Science, 2025)
APETALA1 (AP1), a member of the MADS-box transcription factor family, plays a pivotal role in floral meristem identity and organ formation. In this study, we identified and cloned a novel AP1 homolog gene, EjAP1-like1, from loquat. The gene encodes a 262-amino acid protein with a typical MADS-box domain and shares close phylogenetic relationships with known flowering-related AP1 homologs, suggesting a conserved role in flowering regulation. Promoter analysis revealed multiple cis-acting elements responsive to light, GA, MeJA, and drought. Expression profiling showed that EjAP1-like1 is highly expressed in the shoot apical meristem during floral induction, and its expression is modulated by GA3 treatment and short-day photoperiod. Subcellular localization confirmed its nuclear localization. Moreover, ectopic expression of EjAP1-like1 in Arabidopsis thaliana led to significantly earlier flowering. Collectively, these findings highlight EjAP1-like1 as a potential floral inducer in loquat and offer a useful genetic resource for understanding and manipulating flowering time in woody fruit crops.